2022
DOI: 10.1007/s40520-022-02159-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with and 1-year outcomes of fear of falling in a geriatric post-hip fracture assessment

Abstract: Background Hip fracture causes not only physical injury but also psychological trauma. Fear of falling (FoF) is related to poor recovery, loss of mobility and mortality. There is limited data on the clinical factors affecting post-hip fracture FoF and its consequences. Objective To investigate the factors associated with and 1-year outcomes of post-hip fracture FoF. Methods An observational prospective cohort study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The results of falls only showed that the risk of mobility limitations was not significant in older adults who lived alone. To date, only few studies have investigated the relationship between living alone, falls, FOF, and mobility ( 42 , 43 ). In general, living alone has an impact on the frequency of falls and the occurrence of FOF in older adults ( 20 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of falls only showed that the risk of mobility limitations was not significant in older adults who lived alone. To date, only few studies have investigated the relationship between living alone, falls, FOF, and mobility ( 42 , 43 ). In general, living alone has an impact on the frequency of falls and the occurrence of FOF in older adults ( 20 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Falls represent 38% of adverse events in the hospital setting, constituting a relevant event [ 15 ]. A percentage between 4 and 6% of falls causes major injuries, i.e., bleeding, fractures, and subdural hemorrhage [ 16 ]. The compression of the patient’s fall risk in a healthcare facility is an indicator of the quality of the healthcare service and cannot be achieved without specific training of the healthcare personnel to improve the competence in the prevention and management of falls, but also the awareness of the risk [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…All studies that performed correlations found a significant, small to large correlation between FoF and function (Table 6). Three cross-sectional studies found associations remained significant after controlling for covariates, at least for some analyses [59][60][61]. Two prospective studies found that FoF does predict future functional performance when assessed a few weeks to 6 months later [18,55].…”
Section: Associations With Measures Of Physical Function or Performancementioning
confidence: 99%